Immune-Protective Formulations and Process Strategies for Improved Survival and Function of Transplanted Islets - Shi, Yannan; Zhao, Ying-Zheng; Jiang, Zhikai; Wang, Zeqing; Wang, Qian; Kou, Longfa; Yao, Qing (Frontiers in Immunology, 2022)
Type 1 diabetes (T1D) is an autoimmune disease caused by the immune system attacking and destroying insulin-producing β cells in the pancreas. Islet transplantation is becoming one of the most promising therapies for T1D patients. However, its clinical use is limited by substantial cell loss after islet infusion, closely related to immune reactions, including instant blood-mediated inflammatory responses, oxidative stress, and direct autoimmune attack. Especially the grafted islets are not only exposed to allogeneic immune rejection after transplantation but are also subjected to an autoimmune process that caused the original disease. Due to the development and convergence of expertise in biomaterials, nanotechnology, and immunology, protective strategies are being investigated to address this issue, including exploring novel immune protective agents, encapsulating islets with biomaterials, and searching for alternative implantation sites, or co-transplantation with functional cells. These methods have significantly increased the survival rate and function of the transplanted islets. However, most studies are still limited to animal experiments and need further studies. In this review, we introduced the immunological challenges for islet graft and summarized the recent developments in immune-protective strategies to improve the outcomes of islet transplantation.